Modelagem semi-empírica da distribuição de água de aspersores autopropelidos sob diferentes condições de vento - Oliveira, Henrique Fonseca Elias de (2008)
Water application uniformity is an important aspect of irrigation system performance. A non uniform application results in economic losses and compromises environmental quality. Water application uniformity of travel irrigation machines depends on the combination of several factors including: (i) sprinkler type and operational characteristics (nozzle size, working pressure, jet angle, and wetted sector angle), (ii) towpath spacing, and (iii) wind speed and direction. In this study, a semi empirical model that predicts the distortion by wind of raingun application patterns, was used to adjust the empirical parameters necessary to predict water application pattern of the PLONA-RL250 gun sprinkler operating under different wind conditions. This semi-empirical model was calibrated and validated using infield measured wind-distorted water distribution patterns. Values of traveling gun machine Christiansen´s coefficient of uniformity based on infield measured wind-distorted water distributions were compared with values based on simulated wind-distorted water distributions showing a good correlation among then (r2 = 0.718 and average absolute deviation of 5.38%). Several simulations were run in order to identify traveling gun irrigation configurations that achieve optimal irrigation uniformities. Simulations were grouped according to four typical radial application patterns ( I, II, III and IV), identified through clustering analysis, that were used to represent the 160 possible pressure-nozzle combinations of the PLONA- RL250 gun sprinkler. Simulated results indicated that (i) maximum towpath spacing necessary to achieve Christiansen´s coefficient values above 80% depends on sprinkler radial application pattern, wind speed and wind direction; (ii) traveling irrigation uniformity is more affected by a wind direction parallel to towpath than other directions; (iii) under any wind condition, there is no indication that irrigation performance under a 2700 wetted sector is better than that under 3600.